Case study of thyroid dysfunction associated with polycystic ovarian syndrome (PCOS) - Kaavya M; Nithin Palanisami P S; Thakur, Rashmi; Saru Sree Mu (Creative Pharma Assent, 2023)
Background: In recent times, there's a noticeable rise in endocrine dysfunctions, with increasing clinical resemblance between PCOS and autoimmune thyroid disease. The exact cause of this association remains uncertain, but these conditions share a reciprocal relationship. While they exhibit common clinical features, risk factors, and pathophysiological abnormalities, the root causes differ. Polycystic ovaries can be a manifestation of hypothyroidism, making it necessary to rule out hypothyroidism before diagnosing PCOS. Common factors like increased adipose tissue, insulin resistance, high leptin, and abnormal autoimmunity play a vital role in linking these conditions. These shared signs and symptoms emphasize the association between PCOS and hypothyroidism, though the etiopathological basis of this complex relationship is not fully established. Methodology: Cross-Sectional study of 200 patients involved after history, examination. Statistical analysis by SPSS v.22. Result: In this study, we aimed to evaluate thyroid function in PCOS patients using serum TSH levels and estimate the prevalence of hypothyroidism. We also examined prolactin levels in diagnosed PCOS patients, considering criteria like age distribution, BMI, clinical manifestations, fertility status, and thyroid status. Conclusion: Our findings suggest that PCOS is more prevalent in patients with thyroid disorders such as autoimmune thyroiditis and subclinical hypothyroidism compared to the general population. Additionally, PCOS increases the risk of cardiovascular diseases like hypertension and dyslipidemia. Subclinical hypothyroidism with PCOS further elevates the risk of hypertension compared to euthyroid PCOS patients. The study reveals that thyroid dysfunction occurs in 29.0% of PCOS patients, emphasizing importance of screening for thyroid abnormalities in PCOS patients.